Design of multi-component periodic maintenance programs with single-component models. (3rd July 2018) - Arts, Joachim; Basten, Rob
ABSTRACT: Capital assets, such as wind turbines and ships, require maintenance throughout their long lifetimes. Assets usually need to go offline to perform maintenance, and such downs can be either scheduled or unscheduled. Since different components in an asset have different maintenance policies, it is key to have a maintenance program in place that coordinates the maintenance policies of all components, to minimize costs associated with maintenance and downtime. Single-component maintenance policies have been developed for decades, but such policies do not usually allow coordination between different components within an asset. We study a periodic maintenance policy and a condition-based maintenance policy in which the scheduled downs can be coordinated between components. In both policies, we assume that at unscheduled downs, a minimal repair is performed to keep the unscheduled downtime as short as possible. Both policies can be evaluated exactly using renewal theory, and we show how these policies can be used as building blocks to design and optimize maintenance programs for multi-component assets.